NEW SPECIES OF NEMATODA, PLATYHELMINTHES AND OTHER RELATED GROUPS DESCRIBED IN 2012: A GLOBAL ASSESSMENT OF TAXONOMIC EFFORT - Zamorano, Pablo (2014)
From the records considered in this work, it was established that in 2012 were described 478 new species of Nematoda and Platyhelminthes, with 240 and 238 species respectively. The description of new species was reported in 303 articles published in 63 scientific journals around the world. The descriptions recorded that 65 countries were established as type locality with India, Brazil, Australia and China being the countries with higher proportion of 46 described species (9.62 % of total), 41 (8.58%), 31 (6.49%) and 30 (6.28 %), respectively. This description was provided by 207 taxonomists placed as first author in the articles (107 for Nematoda and 100 for Platyhelminthes) with an average rate for 2012 of 2.24 species of Nematoda per first author and 1.41 per item; while Platyhelminthes the average rate in 2012 was 2.38 per author and 1.79 per article. Additionally the results for related taxa are briefly presented.